Analisis Pelaksanaan Evaluasi Pembelajaran Berbasis Tematik di Madrasah Ibtidaiyah Kabupaten Rejang Lebong - Susilawati Susilawati; Syaripah Syaripah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study uses this type of research is qualitative research by conducting field surveys on the implementation of thematic-based learning evaluations. The subject of this study used a purposive sample of all Rejang Lebong Madrasah (MI) Districts consisting of 4 (four) state schools and 8 (eight) schools with private status. It is known that the results of his Thematic RPP are categorized as